2010
DOI: 10.15288/jsad.2010.71.201
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant Use, Inhalant-Use Disorders, and Antisocial Behavior: Findings From the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC)

Abstract: ABSTRACT. Objective:Few studies have explored the topography of antisocial behavior in a nationally representative sample of inhalant users. We examined (a) the lifetime prevalence of 20 childhood and adult antisocial behaviors in inhalant users with inhalant-use disorders (IUD+) and without IUDs (IUD−); (b) the nature and strength of associations between inhalant use, IUDs, and specifi c antisocial behaviors in multivariate analyses; and (c) the relationships between inhalant use, IUDs, and antisocial behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
(19 reference statements)
0
16
1
1
Order By: Relevance
“…Prevalence of conduct disorder is high among volatile substance misusers and this disorder has been shown to affect treatment outcomes (Howard, Perron, Vaughn, Bender, & Garland, 2010;Sakai et al, 2006). Presence of conduct disorder might have affected abstinence rates in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…Prevalence of conduct disorder is high among volatile substance misusers and this disorder has been shown to affect treatment outcomes (Howard, Perron, Vaughn, Bender, & Garland, 2010;Sakai et al, 2006). Presence of conduct disorder might have affected abstinence rates in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…One recent nationally representative study concluded that volatile substance misusers, particularly those engaged in more severe use, evidenced pervasively elevated levels of antisocial behavior, especially interpersonal violence and early-onset conduct problems (Howard, Perron, Vaughn, Bender, & Garland, 2010). Surveys of adolescent volatile substance misusers indicate that they tend to behave more impulsively and fearlessly, and report more substance use than non-volatile substance misusers , and lower levels of self-esteem, family support, and family cohesiveness observed among volatile substance misusers relative to non-volatile substance misusers (Howard & Jenson, 1999).…”
Section: Psychiatric Correlatesmentioning
confidence: 99%
“…Düşünen Adam The Journal of Psychiatry and Neurological Sciences, Volume 27, Number 1, March 2014 disorders and other substance abuse disorders are more frequent in persons who abuse volatile substances (5,6). Psychotic symptoms in these persons must be distinct due to substance intoxications.…”
Section: Introductionmentioning
confidence: 99%